Efficacy of bezlotoxumab in preventing the recurrence of Clostridioides difficile infection: an Italian multicenter cohort study. (June 2023) - Meschiari, Marianna; Cozzi-Lepri, Alessandro; Cervo, Adriana; Granata, Guido; Rogati, Carlotta; Franceschini, Erica; Casolari, Stefania; Tatarelli, Paola; Giacobbe, Daniele Roberto; Bassetti, Matteo; Pinna, Simone Mornese; De Rosa, Francesco Giuseppe; et al.
Highlights: Bezlotoxumab (BEZ) is more effective than standard of care alone in preventing the recurrence of Clostridioides difficile infection (rCDI). BEZ reduces the risk of rCDI by 60% in a selected population with multiple risk factors. This reduction is more evident considering a composite outcome (rCDI and/or death). BEZ is effective regardless of age, type of standard of care, number of risk factors, and previous Clostridioides difficile infection. In patients aged <70 years and treated with fidaxomicin, the benefit of BEZ is attenuated. Abstract: Objectives: Bezlotoxumab (BEZ) is a promising tool for preventing the recurrence of Clostridioides difficile infection (rCDI). The aim of the study was to emulate, in a real-world setting, the MODIFY trials in a cohort of participants with multiple risk factors for rCDI treated with BEZ in addition to the standard of care (SoC) versus SoC alone. Methods: A multicenter cohort study was conducted including 442 patients with Clostridioides difficile infection from 2018 to 2022, collected from 18 Italian centers. The main outcome was the 30-day occurrence of rCDI. The secondary outcomes were (i) all-cause mortality at 30 days (ii) and the composite outcome (30-day recurrence and/or all-cause death). Results: rCDI at day 30 occurred in 54 (12%): 11 in the BEZ + SoC group and 43 treated with SoC alone (8% vs 14%, odds ratio [OR] = 0.58, 95% confidence interval [CI]: 0.31-1.09, P = 0.09). The difference between BEZ + SoC versus SoC was statistically significant after controlling for confounding factors (adjusted OR = 0.40, 95% CI: 018-0.88, P = 0.02) and even more using the composite outcome (adjusted OR = 0.35, 95% CI: 0.17-0.73, P = 0.005). Conclusion: Our study confirms the efficacy of BEZ + SoC for the prevention of rCDI and death in a real-world setting. BEZ should be routinely considered among participants at high risk of rCDI regardless of age, type of Clostridioides difficile infection therapy (vancomycin vs fidaxomicin), and number of risk factors.